2023
DOI: 10.1038/s41467-023-43544-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin regulates NO-dependent cilia motility and organ laterality during development

Elizabeth R. Rochon,
Jianmin Xue,
Manush Sayd Mohammed
et al.

Abstract: Cytoglobin is a heme protein with unresolved physiological function. Genetic deletion of zebrafish cytoglobin (cygb2) causes developmental defects in left-right cardiac determination, which in humans is associated with defects in ciliary function and low airway epithelial nitric oxide production. Here we show that Cygb2 co-localizes with cilia and with the nitric oxide synthase Nos2b in the zebrafish Kupffer’s vesicle, and that cilia structure and function are disrupted in cygb2 mutants. Abnormal ciliary funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…It is, therefore, conceivable that the interaction between PITX2 and ADGB, two factors with otherwise no apparent co-expression (https://www.proteinatlas.org/ENSG00000164093-PITX2/tissue) [31] (Supplemental Figure S8), is temporally restricted to early stages of embryogenesis during the determination of left-right symmetry. Recent work demonstrated that another globin protein family member, cytoglobin, regulates left-right symmetry in zebrafish [36]. Future studies in our Adgb knockout mouse model [6] will show whether Adgb may also play a role in the establishment of left-right symmetry.…”
Section: Discussionmentioning
confidence: 90%
“…It is, therefore, conceivable that the interaction between PITX2 and ADGB, two factors with otherwise no apparent co-expression (https://www.proteinatlas.org/ENSG00000164093-PITX2/tissue) [31] (Supplemental Figure S8), is temporally restricted to early stages of embryogenesis during the determination of left-right symmetry. Recent work demonstrated that another globin protein family member, cytoglobin, regulates left-right symmetry in zebrafish [36]. Future studies in our Adgb knockout mouse model [6] will show whether Adgb may also play a role in the establishment of left-right symmetry.…”
Section: Discussionmentioning
confidence: 90%